Nanoconfinement matters in humidified CO 2 interaction with metal silicates - Zare, Siavash; Uddin, K. M. Salah; Funk, Andreas; Miller, Quin R. S.; Abdolhosseini Qomi, Mohammad Javad (Environmental science. Nano, 2022)
With enigmatic observations of enhanced reactivity of wet CO 2 -rich fluids with metal silicates, the mechanistic understanding of molecular processes governing carbonation proves critical in designing secure geological carbon sequestration and economical carbonated concrete technologies. Here, we use the first principle and classical molecular simulations to probe the impact of nanoconfinement on physicochemical processes at the rock–water–CO 2 interface. We choose nanoporous calcium–silicate–hydrate (C–S–H) and forsterite (Mg 2 SiO 4 ) as model metal silicate surfaces that are of significance in cement chemistry and geochemistry communities, respectively. We show that while a nanometer-thick interfacial water film persists at unsaturated conditions consistent with in situ infrared spectroscopy, the phase behavior of the water–CO 2 mixture changes from its bulk counterpart depending on the surface chemistry and nanoconfinement. We also observe enhanced solubility at the interface of water and CO 2 phases, which could amplify the CO 2 speciation rate. Through free energy calculations, we show that CO 2 could be found in a metastable state near the C–S–H surface, which can potentially react with surface water and hydroxyl groups to form carbonic acid and bicarbonate. These findings support the explicit consideration of nanoconfinement effects in reactive and non-reactive pore-scale processes.